Autoregulation of RNA Helicase Expression in Response to Temperature Stress in Synechocystis sp. PCC 6803 - Rosana, Albert Remus R. (Public Library of Science, 2012)
RNA helicases are ubiquitous enzymes whose modification of RNA secondary structure is known to regulate RNA function. The pathways controlling RNA helicase expression, however, have not been well characterized. Expression of the cyanobacterial RNA helicase, crhR, is regulated in response to environmental signals that alter the redox poise of the electron transport chain, including light and temperature. Here we analyze crhR expression in response to alteration of abiotic conditions in wild type and a crhR mutant, providing evidence that CrhR autoregulates its own expression through a combination of transcriptional and post-transcriptional mechanisms. Temperature regulates crhR expression through alteration of both transcript and protein half-life which are significantly extended at low temperature (20°C). CrhR-dependent mechanisms regulate both the transient accumulation of crhR transcript at 20°C and stability of the CrhR protein at all temperatures. CrhR-independent mechanisms regulate temperature sensing and induction of crhR transcript accumulation at 20°C and the temperature regulation of crhR transcript stability, suggesting CrhR is not directly associated with crhR mRNA turnover. Many of the processes are CrhR- and temperature-dependent and occur in the absence of a correlation between crhR transcript and protein abundance. The data provide important insights into not only how RNA helicase gene expression is regulated but also the role that rearrangement of RNA secondary structure performs in the molecular response to temperature stress. We propose that the crhR-regulatory pathway exhibits characteristics similar to the heat shock response rather than a cold stress-specific mechanism.